2020
DOI: 10.3390/ma13061451
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cu Content on Structure and Magnetic Properties in Fe86-xCuxB14 Alloys

Abstract: Influence of Cu content on thermodynamic parameters (configurational entropy, Gibbs free energy of mixing, Gibbs free energy of amorphous phase formation), crystallization kinetics, structure and magnetic properties of Fe86-xCuxB14 (x = 0, 0.4, 0.55, 0.7, 1) alloys is investigated. The chemical composition has been optimized using a thermodynamic approach to obtain a minimum of Gibbs free energy of amorphous phase formation (minimum at 0.55 at.% of Cu). By using differential scanning calorimetry method the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…The ∆G amoprh from the Cu content dependence shape is asymmetric, and, for Cu = 0% and Cu = 1.5%, the same ∆G amoprh value is observed. It was also noticed that, obtained in this work, the minimum value ∆G amoprh = −21.12 kJ/mol at Cu = 0.6% is more negative than for the Fe 86-x Cu x B 14 system with ∆G amoprh = −20.03 kJ/mol at Cu = 0.55% studied previously [6]. Basing on obtained thermodynamic calculation results, four selected compositions were taken into consideration in the experimental part: Fe 85-x Cu x B 15 , x = 0,0.6,1.2,1.5.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The ∆G amoprh from the Cu content dependence shape is asymmetric, and, for Cu = 0% and Cu = 1.5%, the same ∆G amoprh value is observed. It was also noticed that, obtained in this work, the minimum value ∆G amoprh = −21.12 kJ/mol at Cu = 0.6% is more negative than for the Fe 86-x Cu x B 14 system with ∆G amoprh = −20.03 kJ/mol at Cu = 0.55% studied previously [6]. Basing on obtained thermodynamic calculation results, four selected compositions were taken into consideration in the experimental part: Fe 85-x Cu x B 15 , x = 0,0.6,1.2,1.5.…”
Section: Resultssupporting
confidence: 81%
“…The magnetic properties of soft magnetic materials depend on the chemical composition and proper annealing process [4]. The high saturation induction nanocrystalline alloy systems including FeBCu [5][6][7], FeSiBCu [8], and FeSiBPCu [9] were successfully developed over the last two decades. For all of these alloys, the maximum values of magnetic saturation were obtained for Cu content chemical compositions using the conventional heating rate of 10-40 • C/min and subsequent isothermal annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that a small addition of copper reduces the Gibbs free energy of amorphous phase formation (∆G amorph ), which has a minimum for 0.55 at.% Cu content. Moreover, with such a copper content, the minimum value of the real and imaginary magnetic permeability was recorded and it is a "breakpoint" in the magnetic properties of the material [28]. It is worth noting, that the optimal Cu content depends on the chemical composition and the Cu effect on the properties of multicomponent amorphous and nanocrystalline iron-based alloys is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Soft magnetic materials (SMMs) are still of great interest in motor [1], power converter [2,3], switched-mode power supplies [4] and sensor applications [5]. Currently, amorphous and nanocrystalline Fe-, Co-and Ni-based alloys (or combination of ferromagnetic metals) can be used for this purpose [6][7][8][9]. There are two main approaches in developing and optimizing of novel SMMs.…”
Section: Introductionmentioning
confidence: 99%